2020
DOI: 10.1080/0167482x.2020.1806819
|View full text |Cite
|
Sign up to set email alerts
|

The level of anxiety in infertile women whose ART cycles are postponed due to the COVID-19 outbreak

Abstract: Aim: This study evaluated the level of fear and anxiety related to the COVID-19 outbreak, in infertile women whose ART cycles were delayed due to the pandemic. Materials and methods: An online survey was sent to women whose ART cycles were postponed due to the COVID-19 outbreak between April and May 2020. The study population were 101 participants. The main outcome measure is to determine the levels of fear and anxiety in infertile women by using the Spielberger State-Trait Anxiety Inventory (STAI-T and STAI-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 30 publications
4
40
0
Order By: Relevance
“…Stress symptoms were also more frequent in patient above 35 years old. Same trend was found in infertile Turkish women ( 28 ). Advanced maternal age is known to have a significant impact on reproductive outcomes with the physiological decrease of ovarian reserve over time.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Stress symptoms were also more frequent in patient above 35 years old. Same trend was found in infertile Turkish women ( 28 ). Advanced maternal age is known to have a significant impact on reproductive outcomes with the physiological decrease of ovarian reserve over time.…”
Section: Discussionsupporting
confidence: 74%
“…In Turocy et al, cancellation of fertility treatment upset infertile couples ( 25 ). Regarding the COVID-19 studies, in different countries, an increase of emotional distress and anxiety were found in infertile couple ( 26 , 27 ), especially in women ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…In another study conducted in 627 Italian infertile couples who were candidates for assisted reproduction treatments, confinement had produced a moderate/severe psychological impact, with these women reporting higher levels of anxiety and depression ( 33 ). Studies carried out during the pandemic on infertile women from other countries, such as the US ( 55 , 56 ), Turkey ( 57 ), the United Kingdom ( 58 ), or Canada ( 59 ) also showed results consistent with an increase in anxiety and depression. When the reproductive service was reopened, we observed a significant decrease in the overall HADS questionnaire score.…”
Section: Discussionmentioning
confidence: 91%
“…There is growing evidence that most infertile women postpone examination and treatment during the pandemic, which may have a negative impact on their lives ( 17 , 29 ). It has previously been reported that among infertile women whose ART cycle has been postponed due to the pandemic, women older than 35 years have higher levels of anxiety ( 30 ). Despite the COVID-19 pandemic, infertility is still among the top stressors, which can be comparable to the pressure caused by the epidemic itself ( 16 ).…”
Section: Discussionmentioning
confidence: 99%